2009
DOI: 10.1016/j.brainres.2009.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Two types of inhibitory influences target different groups of taste-responsive cells in the nucleus of the solitary tract of the rat

Abstract: Electrical stimulation of the chorda tympani nerve (CT; innervating taste buds on the rostral tongue) is known to initiate recurrent inhibition in cells in the nucleus of the solitary tract (NTS, the first central relay in the gustatory system). Here, we explored the relationship between inhibitory circuits and the breadth of tuning of taste-responsive NTS neurons. Initially, NTS cells with evoked responses to electrical stimulation of the CT (0.1 ms pulses; 1 Hz) were tested with each of four tastants (0.1 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Similar subsets of neurons that have higher cut-off frequencies that pass the afferent input relatively unchanged have been described in the caudal NST (Mifflin, 2001) and also in the paired pulse study of CT-rNST synapses (Rosen and DiLorenzo, 2009). …”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Similar subsets of neurons that have higher cut-off frequencies that pass the afferent input relatively unchanged have been described in the caudal NST (Mifflin, 2001) and also in the paired pulse study of CT-rNST synapses (Rosen and DiLorenzo, 2009). …”
Section: Discussionsupporting
confidence: 54%
“…A more recent similar study of second order rNST neurons to paired pulse stimulation of the CT reported frequency dependent synaptic depression (Rosen and DiLorenzo, 2009). In this in vivo study rNST neurons were isolated and responses to tongue stimulation with chemicals determined and then responses of the same neurons were measured to paired pulse stimulation of the CT at pulse intervals ranging from 10 to 2000 ms (i.e.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, application of the GABA antagonist bicuculline can broaden the breadth of tuning of taste-responsive rNTS cells. Moreover, inhibitory interactions in rNTS may enhance and stabilize the temporal structure of taste-evoked spike trains (Rosen and Di Lorenzo, 2009). The caveat to what is known about the functionality of GABA-driven inhibition in neural coding of taste is that it is all derived from studies in anesthetized subjects; the function of inhibition in taste coding in awake subjects may be different.…”
Section: Introductionmentioning
confidence: 99%